Maqâṣid Al-Qur’ân In The Interpretation of M. Quraish Shihab About The Verse of Social Media Usage - Johar Arifin; Ilyas Husti; Khairunnas Jamal; Afriadi Putra (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
This article aims to explain maqâṣid al-Qur’ân according to M. Quraish Shihab and its application in interpreting verses related to the use of social media. The problem that will be answered in this article covers two main issues, namely how the perspective of maqâṣid al-Qur’ân according to M. Quraish Shihab and how it is applied in interpreting the verses of the use of social media. The method used is the thematic method, namely discussing verses based on themes. Fr om this study the authors concluded that according to M. Quraish Shihab there are six elements of a large group of universal goals of the al-Qur’ân, namely strengthening the faith, humans as caliphs, unifying books, law enforcement, callers to the ummah of wasathan, and mastering world civilization. The quality of information lies in the strength of the monotheistic dimension which is the highest peak of the Qur’anic maqâṣid. M. Quraish Shihab offers six diction which can be done by recipients of information in interacting on social media. Thus, it aims to usher in the knowledge and understanding of what is conveyed in carrying out human mission as caliph, enlightenment through oral and written, law enforcement, unifying mankind and the universe to the ummah of wasathan, and mastery of world civilization